Identification of measurement instruments used to measure the cultural competence of nurses and nursing students - Avdylaj, Liridon (Obzornik zdravstvene nege, 2022)
Introduction: Measuring cultural competence is a crucial step in evaluating the strategies for the development and achievement of cultural competence in nurses and nursing students. The aim of this systematic literature review was to examine the content and characteristics of available questionnaires and to select the most appropriate questionnaires for assessing cultural competence in nurses and nursing students. Methods: A systematic review of the literature was conducted in the CINAHL, ERIC, EBSCO and ScienceDirect databases. The following English search terms were used: transcultural nursing, culturally competent care, cultural competence, nursing education, questionnaire. The review included original research articles on relevant topics available in full text and published after 2010. Results: Of the 247 articles found, 11 articles were included in the final analysis. Based on their content and psychometric features such as reliability and construct validity, four of the analysed questionnaires were found to be most appropriate for measuring cultural competence in nurses, three questionnaires for measuring cultural competence in nursing students and one questionnaire for measuring cultural competence in nurse educators.Discussion and conclusion: Our analysis shows that some of the questionnaires included in this review are better suited for measuring cultural competence in nurses, while others are more suitable for measuring cultural competence in nursing students. This systematic review of the literature provides a useful starting point for other researchers in the field of cultural competence assessment in selecting appropriate questionnaires for further research.
Keywords: izobraževanje; kulturne kompetence; medicinske sestre; študenti; zdravstvena nega